2017
DOI: 10.1007/s12032-016-0880-3
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 acts as a foe to MIA PaCa-2 pancreatic cancer

Abstract: IL-33 is a member of the IL-1 family of cytokines, and no study has been performed to address its direct anti-tumor effect. This study is designed to investigate whether IL-33 has any direct effect on pancreatic cancer. Clonogenic survival assay, immunohistochemistry, TUNEL staining, proliferation, caspase-3 activity kits and RT-PCR were used to evaluate the effects of IL-33 on cell survival, proliferation and apoptosis of a pancreatic cancer cell line, MIA PaCa-2. We found that the percentage of colonies of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 50 publications
6
47
1
Order By: Relevance
“…IL-33 has been identified as a useful biomarker in the diagnosis or prediction of prognosis in non-small cell lung cancer (11). Interestingly, other studies have suggested that IL-33 has an anti-tumor effect in colon cancer (12,13) and our previous study on pancreatic and colon cancer echoes these findings (14). This suggests the complex role of IL-33 in the pathogenesis of neoplasia.…”
Section: Introductionsupporting
confidence: 68%
“…IL-33 has been identified as a useful biomarker in the diagnosis or prediction of prognosis in non-small cell lung cancer (11). Interestingly, other studies have suggested that IL-33 has an anti-tumor effect in colon cancer (12,13) and our previous study on pancreatic and colon cancer echoes these findings (14). This suggests the complex role of IL-33 in the pathogenesis of neoplasia.…”
Section: Introductionsupporting
confidence: 68%
“…This indicates that the role of IL-33 in neoplasia is complex and further studies are required to address the exact role of IL-33 in different cancer types. Previously published data demonstrated that IL-33 inhibited proliferation and induced apoptosis of pancreatic cancer cells, and laid the groundwork for the present study ( 12 ).…”
Section: Introductionmentioning
confidence: 72%
“…ST2 also has a significant effect on the pathogenesis of several diseases, including inflammation, allergies, fibrillation, cardiac hypertrophy and rheumatoid arthritis (22). Numerous studies have suggested that ST2 expression is associated with carcinogenesis and tumor progression in multiple cancer types (13)(14)(15)(16)22). ST2 has been shown to regulate innate and acquired immunity in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that ST2L/IL-33 participates in a number of inflammatory immune response processes associated with asthma, allergic diseases, autoimmune diseases, cardiovascular diseases and other conditions associated with acute heart failure, myocardial infarction, respiratory failure and acute trauma (11,12). Previous studies revealed that ST2 was involved in the pathogenesis and prognosis of multiple types of cancer, including glioblastoma, breast and pancreatic cancer, and leukemia (13)(14)(15)(16). However, to the best of our knowledge, the role of ST2 in gastric cancer remains to be elucidated.…”
Section: Decreased St2 Expression Is Associated With Gastric Cancer Pmentioning
confidence: 99%